BPD Communication Strategy in Increasing Community Participation in the Development of Gembung Raya Village - Meiyopan Bui Putra; Anis Endang Sri Murwani; Bayu Risdiyanto (Journal of Law, Social Science, and Management Review, 2026)
The communication strategy of the Village Consultative Body (BPD) plays an important role in encouraging community participation in village development processes. Ineffective communication planning may lead to low levels of community involvement in development programs implemented by the village government. This study aims to analyze the communication strategy of the Village Consultative Body (BPD) in increasing community participation in the development of Gembung Raya Village, Napal Putih District, North Bengkulu Regency. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, field observations, and documentation. The research informants consisted of the head of BPD, community leaders, the head of the youth organization, and members of the community in Gembung Raya Village who were selected using purposive sampling techniques. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing and verification. The results of the study indicate that the communication strategy implemented by BPD in increasing community participation has not been optimal. In the stage of identifying the audience, the understanding of community characteristics and needs has not been comprehensive because village deliberations tend to involve only certain groups. In the stage of message formulation, development information is delivered through deliberation meetings using relatively simple language; however, it has not fully reached all community members. In the stage of determining the communication method, communication is mainly conducted through village meetings and direct interactions, yet community participation remains relatively low. In addition, the use of communication media is still limited to traditional methods such as invitation letters and face-to-face communication without utilizing broader communication media. Therefore, BPD is expected to evaluate and improve its communication strategies by developing more inclusive, transparent, and participatory communication and by utilizing more diverse communication media in order to enhance community participation in sustainable village development.